Southern Africa : in search of a common future : from the conference to a community - Mandaza, Ibbo (SADC GaboroneBW, 1994)
Describes the foundation of the Southern African Development Coordination Conference (SADCC) and the history of its first ten years and its transformation into the Southern African Development Community (SADC). Discusses the role of SADC in the member states, South Africa and the world at large.